2017
DOI: 10.1007/s13205-017-1000-6
|View full text |Cite
|
Sign up to set email alerts
|

Expression of STK11 gene and its promoter activity in MCF control and cancer cells

Abstract: Serine/threonine kinase gene (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 23 publications
0
1
0
Order By: Relevance
“…The extrinsic pathway was induced through stk-11 gene expression. It is demonstrated that stk-11 physically associates with p53 and regulates a specific p53-dependent extrinsic apoptosis pathway [40]. Stk-11 protein is present in the cytoplasm as well as the nucleus and migrates to mitochondria during apoptosis [41].…”
Section: Discussionmentioning
confidence: 99%
“…The extrinsic pathway was induced through stk-11 gene expression. It is demonstrated that stk-11 physically associates with p53 and regulates a specific p53-dependent extrinsic apoptosis pathway [40]. Stk-11 protein is present in the cytoplasm as well as the nucleus and migrates to mitochondria during apoptosis [41].…”
Section: Discussionmentioning
confidence: 99%
“…The LKB1 promoter reporter construct was generated by amplifying a 3995-bp fragment of the LKB1 promoter using primers LKB1 prom-XhoI-F 5 -CGGGAATCT CGAGTTGGAAATTCAGTG TGTAGGGCA-3 and LKB1 prom-HindIII-R 5-AAAGCGCAAG CTTCAACAAAAACCCCA AAAGGA-3 resulting in amplification of a product containing XhoI and HindIII restriction enzyme cleavage sites to clone into pGL3-basic firefly luciferase expression vector (Promega, U.S.A.), forming STK11-pGL3 after enzymatic digestion [22].…”
Section: Dual Luciferase Reporter Assaymentioning
confidence: 99%